Characteristics and contraceptive outcomes of women seeking medical or surgical abortion in reproductive health clinics in Cambodia - Chris Smith; Rachel H. Scott; Caroline Free; Tansy Edwards (BMC, 2019)
Abstract Background Since the approval of medical abortion in Cambodia in 2010, the proportion of women reporting an abortion has increased. We describe the characteristics and contraceptive outcomes of women seeking medical abortion compared to surgical abortion at four reproductive health clinics in Cambodia. Methods Secondary data analysis using data collected in the MObile Technology for Improved Family Planning (MOTIF) trial, a single blind, randomized trial of a personalized, mobile phone-based intervention designed to support post-abortion family planning in Cambodia. Baseline interviews were conducted after women had received post-abortion family planning counselling at the clinic, and follow-up interviews were conducted at 4 and 12 months. We used multivariable logistic regression to assess associations between abortion type and baseline characteristics, contraceptive uptake, repeat pregnancy and repeat abortion. We conducted an exploratory analysis to compare the timing of initiation of long-acting (LA) contraception between women having medical versus surgical abortion over the four-month post-abortion period. Results Of the 500 women who participated in the trial, 41% had a medical abortion. In multivariate analyses, women undergoing medical abortion were more likely to be urban residents, have a higher level of education, be undecided or not intending to use family planning, and be undecided or intending to have another child. There was no association between type of abortion and contraceptive uptake, repeat pregnancy or repeat abortion. Women who had medical abortion initiated LA contraception post abortion later than women who had surgical abortion. Conclusions Our results suggest women having a medical abortion in Cambodia have different baseline characteristics and had delayed uptake of contraception compared to women having a surgical abortion. However, we cannot draw conclusions on the direction of associations and causality. Further research is recommended to explore reasons for the observed findings with view to increasing access to abortion and post-abortion contraception.